107th commencement exercises - De La Salle University, Manila (Animo Repository, 1993)
The 107th Commencement Exercises were held with Daniel Lacson Jr. as Signum Meriti Awardee and commencement speaker. There were 845 students who received their baccalaureate, masteral and doctoral degrees.